Diseño de un sistema de riego por aspersión para el cultivo de brócoli (Brassica oleracea var. italica) en barrio La Victoria, parroquia Sucre, cantón y provincia de Loja - Guaillas Gualán, Angel Delicio (2023)
The thesis project entitled: "Design of a sprinkler irrigation system for the cultivation of broccoli (Brassica oleracea var. italica) in the La Victoria neighborhood, Sucre parish, canton and province of Loja", was carried out with the objective of contributing to the sustainable management of irrigation water in the lote bonito property, given that the inhabitants of the place have the cultivation of vegetables as their main source of income, which was a necessity to carry out the present investigation. The surface of the project is 0.64 ha, where a study of the soil profile was carried out at a depth of 1 m, where it presents a loamy texture, with CC of 28.6 % humidity, PMP of 14.8 % humidity. The study area has an effective rainfall of 15.3 mm/month, where complementary sprinkler irrigation will be implemented to satisfy the broccoli crop's water requirement of 3.55 mm/day. In area 1 of the property, a sprinkler will be used that produces 1,397 l/h, with a 10 m separation between sprinklers and 18 m between sides. In area 2, the sprinkler produces 728 l/h, with a 10 m separation between sprinklers. and sides. In the hydraulic design, the total dynamic head was 41.09 m and 20.07 m for area 1 and 2 respectively, and the power of the motor pump required to raise the water to the reservoir is 4 HP, thus guaranteeing the proper functioning of the irrigation system and the necessary supply of water to the crops. Keywords: sprinkler irrigation, agronomic design, hydraulic design.